Ferula tadshikorum Pimenov - introduction, chemical composition and use in folk medicine - Khamraeva, D.T.; Tukhtaeva, D.N.; Khojimatov, O.K.; Bussmann, Rainer W (Ethnobotany Research and Applications, 2023)
Background: This study determined the results of the introduction of the Ferula tadshikorum, and comparatively studied the content of proteins and polysaccharides in leaves and roots in three age individuals. Methods: The work used phenological, protein and polysaccharide chemical analyses, as well as a survey on the use of Ferula tadshikorum among local residents of Surkhandarya region of Uzbekistan. Results: Under the conditions of introduction, phenological observations of the growth and development of Ferula tadshikorum were carried out. Based on 4-year experiments, we concluded that, in contrast to the natural conditions, in Tashkent Botanical Garden a shortening of the duration of stages in juvenile and immature individuals, as well as an increase in the number of virginal individuals, is observed in ontogenesis. For the first time, the chemical composition of roots and leaves was studied in three individuals of different ages: 4-year-old introducents of the virginal stage of development, and natural individuals of medium, mature virginal age. The analysis for the content of protein and protein N found that the average protein content in the roots of the Ferula tadshikorum plant ranged from 2.3% to 7.12%, while in the leaves it ranged from 10.23% to 25.56%. The roots and leaves of mature virginal individuals of Ferula tadshikorum had the greatest nutritional value in terms of total protein content. For the first time, the content of various groups of polysaccharides in the roots and leaves of 3 virginal samples of Ferula tadshikorum was elucidated, and alcohol-soluble sugars, water-soluble polysaccharides, pectin substances and hemicellulose were isolated. According to the monosaccharide composition, the roots contained especially to glucogalactaarabans, the leaves arabinogalactans. Some recipes of folk medicine on the use of leaves and resin for the treatment of certain human diseases are given. Conclusion: For the medicinal plant Ferula tadshikorum, new prospects are opening up for the use in both folk medicine and official medicine. In the future, more in-depth phytochemical studies are needed to identify the therapeutic potential of the Ferula tadshikorum. Keywords. chemical analysis, ethnobotany, Ferula tadshikorum, introduction, leaves, root, polysaccharides, proteins.